A two-stage Genetic Algorithm for joint coordination of spare parts inventory and planned maintenance under uncertain failures - Yu, Vincent F.; Salsabila, Nabila Yuraisyah; Siswanto, Nurhadi; Kuo, Po-Hsun (Applied soft computing, 2022)
The main problem of spare parts management is to maintain the minimal requirement of stock keeping units kept. This research proposes a joint optimization model of multi-item multi-period spare parts inventory management and planned maintenance under uncertain failures in order to balance inventory cost and spare parts availability. This paper presents a Mixed Integer Non-linear Programming formulation of the inventory optimization model under a minimum and maximum inventory policy with stock review intervals. Some studies in the literature have considered aggregating spare parts inventory management as they assume that it will reduce the ordering cost. We consider both independent and aggregate spare parts inventory policies and then combine the formulation with the predictive maintenance interval, which is a replacement action due to uncertain failures under predefined distribution. Furthermore, a novel two-stage Genetic Algorithm is proposed as a sim-heuristic approach to deal with the non-linearity, combinations, and stochasticity of the problem and solve large-scale instances. In the end, we perform a computational study on some instances and a real-world case study to demonstrate the proposed approach’s effectiveness and efficiency. The computational study shows that the independent policy results in lower cost than the aggregate policy, and the proposed Genetic Algorithm performs efficiently for large-scale problems. •Joint optimization of spare parts inventory management and planned maintenance.•A Mixed Integer Nonlinear Programming formulation to find the inventory parameters.•A two-stages Genetic Algorithm simulation of the stochastic failures.•Implementation on a real case study of a Petrochemical Company in Gresik, Indonesia.•Comparison of aggregate and independent inventory and maintenance policies.